KAJIAN LAMA SIMPAN IKAN TONGKOL REBUS DENGAN PERENDAMAN ASAP CAIR TEMPURUNG KELAPA - Moegiratul Amaro; Astini Astini; Nazaruddin Nazaruddin (Universitas Mataram, 2024)
This study aimed to determine the effect of storage boiled mackerel tuna fish through immersion in coconut shell liquid smoke. The method in this research was an experimental method by experimenting in Laboratory. The research design used in this study was a completely randomized design (CRD) with a single factor (storage time: 0 hour, 24 hours, 48 hours, 72 hours, 96 hours and 120 hours) which repeated 3 times to obtain 18 units by smearing on 2% coconut shell liquid smoke for 10 minutes. The observed parameters in this study were pH, water content, total microbes, and scoring and hedonic organoleptic (appearance, aroma, texture and taste) of boiled tuna. The data from the observation were analyzed using Analysis of Variance with real level 5% using Co-stat. if there was a significant difference, the further test was continued using Honestly Significant Difference (HSD) with real level 5%. The results showed that the long storage treatment by immersing coconut shell liquid smoke was able to maintain the quality of boiled tuna for up to 48 hours based on a pH of 5,92; water content 59,17%; microbes total 4,85 log CFU/gr; as well as organoleptic that acceptable by the panelist.